Interpretation Of The Phenomenon Of Heroicity In Homer’s Epistle "ILIADA": The Example Of The Images Of Achilles And Hector - Salimjonova, Dilnavoz (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the concept of heroism in the epic poem "Iliad" through the images of Achilles and Hector. The author compares the character of ancient heroes with the figures of Alpomish and Jaloliddin Manguberdi in Uzbek literature and history. The article covers the issues of personal pride and social duty based on the views of Uzbek and world scientists.